STUDI PENGEMBANGAN KARIER PEGAWAI NEGERI SIPIL PADA BADAN KEPEGAWAIAN DAERAH PROVINSI RIAU - Sari, Weny Kurnia; Tua R.F.S, Harapan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Career development in a government agency or organization is very important for the progress and success of the organization in achieving the planned goals. Career development of Civil Servants carried out must be based on competence, qualifications, performance appraisal. This research was conducted at the Riau Province Regional Personnel Agency. The formulation of the problem in this study was how career development of Civil Servants at the Provincial Civil Service Agency. With the aim of this research is to find out how the career development of Civil Servants in the Regional Personnel Agency of Riau Province.This study uses the concept of career development theory according to Siagian (2005: 207). This study uses qualitative research methods, namely research methods based on thoughts and responses from research informants about the problems examined from the research locus, with the type of phenomenological research which is research that specializes in phenomena and realities that appear to examine the explanations in them. The types of data sources are primary data and secondary data, while research data collection techniques use interview, observation, and documentation techniques. The results of this study are based on the results of the discussion that has been described regarding career development of Civil Servants in the Riau Province Regional Personnel Agency, namely fair treatment in careers, direct supervisor care, information about various promotional opportunities, interests to be promoted, and levels of satisfaction. That fair treatment, information about various promotional opportunities, and satisfaction levels are not maximized, because there are still many employees who have not been promoted in their positions even though these employees have attended training and there are also employees who have not participated in training but they already occupy a position, and lack transparency in procurement promotion which is not in accordance with the principles of career development patterns. Seen career development has not been evenly distributed to every employee, and is supported by the results of interviews with informants in the study.Keywords: Development, Career